Biochar from Swine Solids and Digestate Influence Nutrient Dynamics and Carbon Dioxide Release in Soil. Issue 3 (1st May 2013) - Marchetti, Rosa; Castelli, Fabio
Abstract : Large amounts of livestock manure solids are expected to become available in the near future due to the development of technologies for the separation of the solid fraction of animal effluents. The charring of manure solids for biochar (BC) production represents an opportunity for recycling organic matter (OM) of high nutrient value. The objectives of this study were to evaluate the suitability of BC from swine solids (SS) to improve soil fertility through nutrient supply and decomposition of the OM incorporated into soil and to verify a possible interaction effect on soil nutrient dynamics between digestate application and soil amendment with BC. We monitored at laboratory scale the soil mineral nitrogen (Nmin ) and Olsen phosphorus (POls ) content, and the cumulative carbon dioxide (CO2 –C) release in treatments with or without a supply of digestate obtained from a biogas plant. The experiment was performed in laboratory microcosms during a 3‐mo incubation period. Compared treatments were soil amendments with SS, BC from SS, wood chip, BC from wood chip, and soil with no amendment, each of them with and without incorporation of digestate (10 treatments in total). Soil Nmin levels were unaffected by BC amendments and only increased temporarily when digestate was applied to soil amended with SS or BC from SS. For the same N content, the BC from SS supplied much more POls than the nontreated OM. The amount of cumulative CO2 –C released from soil with BC with or without digestate did not differ from that in the unamended control soil and was lower than that in the soils with noncharred amendments. Soil amendment with BC from SS does not modify soil N availability, whereas it increases the content of P available for crops and reduces the release of CO2 –C from digestate applied to soil for agricultural purposes.